Youth criminal justice law - Bala, Nicholas C. (Essentials of Canadian law)
"A society's response to young offenders conveys important messages about its attitude to youth and has a significant implications for its futue. This book is intended to give an introduction to the laws governing young people who come into conflict with the law. It has a particular focus on Canada's Youth Criminal Justice Act." "While the primary focus of this book is on the legal issues that arise in the youth justice system, the book is premised on the belief that youth justice issues must be understood in a broader context. This book includes some discussion of constitutional, evidentiary, and procedural issues that are relevant to youth justice; it also explores some of the ethical and practical issues that confront lawyers and other professionals working in the youth justice system. The book considers the broader social and political context for issues of adolescent offending and youth justice."--BOOK JACKET